2005
DOI: 10.1128/iai.73.6.3307-3312.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Discovered Mycobacterial Pathogen Isolated from Laboratory Colonies of Xenopus Species with Lethal Infections Produces a Novel Form of Mycolactone, the Mycobacterium ulcerans Macrolide Toxin

Abstract: Mycobacterium ulcerans, the causative agent of Buruli ulcer, produces a macrolide toxin, mycolactone A/B, which is thought to play a major role in virulence. A disease similar to Buruli ulcer recently appeared in United States frog colonies following importation of the West African frog, Xenopus tropicalis. The taxonomic position of the frog pathogen has not been fully elucidated, but this organism, tentatively designated Mycobacterium liflandii, is closely related to M. ulcerans and Mycobacterium marinum, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 27 publications
2
131
0
Order By: Relevance
“…MURD152 is a 2.8-kb DNA fragment deleted from M. ulcerans strain Agy99 (ST17) that spans esxA and esxB, genes encoding key components of the ESX-1 secretion apparatus and virulence factor (4,34). The MURD152 deletion PCR assay confirmed earlier findings that showed that esxA and esxB are absent from M. ulcerans strains from Africa, Australia, and Malaysia but present in other MPM (19,26 (32).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…MURD152 is a 2.8-kb DNA fragment deleted from M. ulcerans strain Agy99 (ST17) that spans esxA and esxB, genes encoding key components of the ESX-1 secretion apparatus and virulence factor (4,34). The MURD152 deletion PCR assay confirmed earlier findings that showed that esxA and esxB are absent from M. ulcerans strains from Africa, Australia, and Malaysia but present in other MPM (19,26 (32).…”
Section: Discussionsupporting
confidence: 64%
“…The recent discovery of MPM that are phenotypically distinct from M. ulcerans in diseased fish and frogs has highlighted the possibility that pMUM is being transferred among different mycobacterial species (19,26). In this report, we show by a systematic genetic approach that all MPM are very closely related to each other and have evolved, not by multiple exchanges of pMUM, but from a common M. marinum progenitor that acquired the plasmid.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It has recently been discovered that mycolactones are produced not only by M. ulcerans but also by a variety of very closely related, pMUM-bearing mycobacteria, collectively referred to as mycolactone-producing mycobacteria (MPM) (Mve-Obiang et al, 2005;Ranger et al, 2006;Yip et al, 2007). Interestingly, different MPM produce mycolactone structural variants that differ in the composition of the acyl side-chain.…”
Section: Introductionmentioning
confidence: 99%